Multifluorescence High‐Resolution Episcopic Microscopy for 3D Imaging of Adult Murine Organs. Issue 10 (5th August 2021) - Walsh, Claire; Holroyd, Natalie A.; Finnerty, Eoin; Ryan, Sean G.; Sweeney, Paul W.; Shipley, Rebecca J.; Walker-Samuel, Simon
Abstract : 3D microscopy of large biological samples (>0.5 cm 3 ) is transforming biological research. Many existing techniques require trade‐offs between image resolution, sample size, and method complexity. A simple robust instrument with the potential to conduct large‐volume 3D imaging currently exists in the form of the optical high‐resolution episcopic microscopy (HREM). However, the development of the instrument to date is limited to single‐fluorescent wavelength imaging with nonspecific eosin staining. Herein, developments to realize the potential of the HREM to become multifluorescent high‐resolution episcopic microscopy (MF‐HREM) are presented. MF‐HREM is a serial‐sectioning and block‐facing wide‐field fluorescence imaging technique, which does not require tissue clearing or optical sectioning. Multiple developments are detailed in sample preparation and image postprocessing to enable multiple specific stains in large samples and show how these enable segmentation and quantification of the data. The application of MF‐HREM is demonstrated in a variety of biological contexts: 3D imaging of whole tumor vascular networks and tumor cell invasion in xenograft tumors up to 7.5 mm 3 at resolutions of 2.75 μm, quantification of glomeruli volume in the adult mouse kidney, and quantification of vascular networks and white‐matter track orientation in adult mouse brain. Abstract : Multifluorescent high‐resolution episcopic microscopy (MF‐HREM) realizes the potential of optical HREM to image whole mouse organs with multiple fluorescence labels in 3D. This simple and robust serial‐sectioning block‐face technique is demonstrated in a range of biological contexts with proposed quantification pipelines.